Urology Practice Acquisitions by Private Equity Firms from 2011–2021. Issue 1 (6th January 2022) - Nie, James; ,; Demkowicz, Patrick C.; ,; Hsiang, Walter; Umer, Waez; Chen, Evan M.; McMahon, Gregory; Kenney, Patrick A.; Breyer, Benjamin N.; Parikh, Ravi; Leapman, Michael S.
Abstract: Introduction: Private equity firms have recently acquired several large urology practices in the United States. As little is known about these acquisitions, we sought to characterize trends in urology practice consolidation. Methods: We compiled urology practice acquisition data via financial databases, news outlets, practice websites, and Internet keyword search for the time period January 1, 2011 through March 15, 2021. For each acquisition, we determined the acquiring group, number of employed urologists, practice locations, and status of ancillary services (pathology, radiology, or surgery centers). We estimated workforce effects based on the 2019 American Urological Association workforce census. Results: We identified 69 independent practice acquisitions in the study period, including 19 (28.4%) by hospital systems, 7 (10.4%) by multispecialty physician groups, 23 (34.3%) by urology practices, and 20 (29.9%) by private equity-backed platforms. Private equity firms initially targeted large urology practices (mean of 60.8±32.6 urologists) with ownership of ancillary services and consolidated local market share through acquisitions of smaller practices (mean of 15.9±14.5 urologists). As of March 2021, we estimate that 7.2% of private practice urologists in the U.S. were employed by one of 5 private equity-backed platforms; over 25% of all urologists practicing in New Jersey and Maryland are employed by a private equity-backed platform. Conclusions: Private equity acquisitions have accelerated to become a dominant form of urology practice consolidation in recent years and have achieved significant market influence in certain regions. Future research should assess the impact of private equity investment on practice patterns, health outcomes, and expenditures.